2019
DOI: 10.1155/2019/8051438
|View full text |Cite
|
Sign up to set email alerts
|

Enterococci Isolated from Trout in the Bukovec Water Reservoir and Čierny Váh River in Slovakia and Their Safety Aspect

Abstract: The aim of this study was to investigate enterococci as lactic acid bacteria and as part of Firmicutes phylum. We focused on the virulence factor, biofilm formation, and antibiotic resistance and also on lactic acid production and enterocin gene detection. Intestinal samples were taken from 50 healthy trout (3 Salmo trutta and 47 Salmo gairdneri) collected in April 2007, 2010, and 2015 from different locations at the Bukovec water reservoir and the Čierny Váh River in Slovakia. Twenty pure colonies were identi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…Lactobacilli and Enterococci play an essential role in the trout GIT microbiota ( Iorizzo et al, 2021 ; Lauková et al, 2019 ), and spore-forming bacilli were reported by many groups as potent probiotics for aquaculture ( Nikiforov-Nikishin et al., 2021 ), which also justified our selection of the strain from our collection of probiotics. At the same time, Escherichia coli and Vibrio spp., while being fish commensal microorganisms, are raising concerns because of the pathogenicity of their representatives (for instance, Mothersill et al, 2015 ), especially when it comes to the possible transfer of antibiotic resistance genes in various environments, including in aquaculture ( Capkin et al, 2015 ).…”
Section: Resultsmentioning
confidence: 95%
“…Lactobacilli and Enterococci play an essential role in the trout GIT microbiota ( Iorizzo et al, 2021 ; Lauková et al, 2019 ), and spore-forming bacilli were reported by many groups as potent probiotics for aquaculture ( Nikiforov-Nikishin et al., 2021 ), which also justified our selection of the strain from our collection of probiotics. At the same time, Escherichia coli and Vibrio spp., while being fish commensal microorganisms, are raising concerns because of the pathogenicity of their representatives (for instance, Mothersill et al, 2015 ), especially when it comes to the possible transfer of antibiotic resistance genes in various environments, including in aquaculture ( Capkin et al, 2015 ).…”
Section: Resultsmentioning
confidence: 95%
“…Samples were seeded in Slanetz–Bartley agar plates and incubated for 48 h at 35°C DD CLSI CLSI 73 (62) E. faecium, 67 E. faecalis, 6 E. faecalis Erythromycin, 3 Tetracycline, 3 Quinupristin–dalfopristin, 6 Ampicillin, 0 Ciprofloxacin, 0 Streptomycin, 0 Kanamycin, 0 Gentamicin, 0 Chloramphenicol, 0 Vancomycin, 0 Teicoplanin, 0 E. faecium Erythromycin, 40 Tetracycline, 10 Quinupristin–dalfopristin, 4 Ampicillin, 3 Ciprofloxacin, 3 Streptomycin, 1 Kanamycin, 2 Gentamicin, 1) Chloramphenicol, 1 Vancomycin, 0 Teicoplanin, 0 Lauková et al. ( 2019 ) Trout ( Salmo trutta ) Trout ( Salmo gairdneri ) Intestinal content 50 Slovakia 2007, 2010, 2015 Standard microbial dilution method (ISO): intestinal content stirred (1: 9) in Ringer solution (pH 7.0), plated onto cultivation medium M‐Enterococcus agar to count colonies of enterococci. Plates were cultivated at 37°C for 48 h DD CLSI CLSI Not reported E. faecium , 3 Not reported specifically for E. faecium but merged for 7 isolates of 4 Enterococcus species Novais et al.…”
Section: Introductionmentioning
confidence: 99%